O ethos e o pathos no discurso publicitário da coca-cola : uma análise verbo e audiovisual - Peixoto, Vanessa de Matos (2014)
Advertising has been changing over the years, language and goals has been modified as society changes. Globalization, as the main factor of these modifications, generates a different demand on communication, creating advertising campaigns that reach this global consumer so different from long ago. In this sense, the purpose of this research is to analyze verbal and visual elements presented on the argumentative strategies in two advertising campaigns from distinct years. The corpus used here will be two television commercials for Coca-Cola aired in 1950 and 2011, respectively, aiming in the first case, a better product acceptance in Brazil and in the second case, a campaign to celebrate the 125 years of existence of the product in the world. It is an analytical, qualitative, and longitudinal study; have indirect data; with and without the involvement of human beings. This analysis showed the importance of multimodality in advertising and its relevance in the outcome of the commercials to the consumers of the product, in this case, Coca-Cola. As well, the presence of ethos and pathos in the development of commercials aiming for more effective communication with potential buyers of the product. As a technical resource it was used literature review and analysis of verbal and visual elements presented in both advertisements. This study is based on the existence and adequacy of what was enunciated, enunciator and the interlocutor of multimodal messages on television commercials for Coca-Cola. Thus, this work creates a reflection on the importance of interlocutor and care for a better adaptation of what is expressed on the commercial; necessary conditions for achieving better results in the enunciator expected goals. Besides promoting reflections on multimodal resources used in advertisements for Coca-Cola as argumentative strategies to persuade the public to consume the product.